Los Derechos Fundamentales y las nuevas tecnologías de la Información y Comunicación: una aproximación - Díaz Colchado, Juan Carlos (2021)
The use of new information and communication technologies in different areas of society is increasing. On one hand, there is no doubt that technology has a positive impact on society.However, on the other, its application cannot be unrestricted, but rather, based on a harmonious reading of the Constitution, it must be limited on the basis of material criteria such as fundamental rights. In this article, the authors analyze the irruption of new technologies –such as big data and algorithms– in the general theory of fundamental rights, delimiting their concepts, foundations, contents, among others. In addition, the authors explore the impact on certain fundamental rights such as personal freedom and privacy. Finally, from a critical point of view, they distinguish when the use of these new technologies in specific situations becomes constitutional or, failing that, unconstitutional.